Community Participation in the Primary Education Development in Pulau Pulau Aru Subdistrict - Soselisa, Hobarth Williams (Opción, 2019)
The aim of this study is to identify the forms, the participation factors, and the community participation model in primary education development in Pulau Pulau Aru through descriptive and qualitative methods. The results of this study were also considered as novel as it shows the community participation model adapted from the traditional customs values of One Furnace Three Stones and Tagalaya. Local government (subdistrict heads and Education Minister), members of the board (commission of education), the private sector (companies) and the public should work in synergy to improve primary education quality in Pulau Pulau Aru, in general and in particular.